Academic response to improving value and reducing waste: A comprehensive framework for INcreasing QUality In patient-oriented academic clinical REsearch (INQUIRE). - Belinda von Niederhäusern; Gordon H Guyatt; Matthias Briel; Christiane Pauli-Magnus (PLoS Medicine)
Background Compelling evidence has demonstrated that a large proportion of investment in biomedical research is wasted; this waste is avoidable. Academic institutions have, thus far, shown limited response to recommendations for increasing value and reducing waste. We formulated an academic response by (i) achieving consensus across a wide range of stakeholder groups on a comprehensive framework for quality of patient-oriented clinical research and (ii) highlighting first successful examples of its operationalization to facilitate waste-reducing strategies at academic institutions. Methods and findings Based on a systematic review of quality definitions, concepts, and criteria in the medical literature (systematic MEDLINE search up to February 15, 2015, with independent and in duplicate article selection) and on stakeholder websites from 13 countries (Australia, Austria, Canada, France, Germany, Italy, Japan, Norway, Spain, Sweden, Switzerland, United Kingdom, and United States), we systematically developed a comprehensive framework for the quality of clinical research. We identified websites through personal contacts with experts in clinical research or public health who also suggested, for each country, websites of the following 7 stakeholder groups: patient organizations; academic research infrastructures; governmental bodies; regulatory agencies; ethics committees; the pharmaceutical industry; and funding agencies. In addition, we searched websites of inter- or supranational bodies involved in clinical research until no further insights emerged. After consolidation of the identified definitions, concepts, and criteria of quality in a basic framework structure, we conducted 4 rounds of an adapted online Delphi process among the same 7 stakeholder groups from 16 countries. The Delphi process ultimately achieved consensus on structure and content. The framework addresses 5 study stages (concept, planning and feasibility, conduct, analysis and interpretation, and reporting and knowledge translation) and includes the following dimensions: (i) protection of patient safety and rights, (ii) relevance/patient centeredness and involvement, (iii) minimization of bias (internal validity), (iv) precision, (v) transparency/access to data, and (vi) generalizability (external validity) of study results. These dimensions interact with 2 promoters-infrastructure and sustainability through education-that include a set of factors that may enhance all listed quality dimensions. Each quality dimension contains specific questions and explanatory items that guide quality assessment at each research stage from conceptualization of the research question through reporting and knowledge translation of study results. In the last survey round, Delphi participants from 9 countries (Austria, Australia, Canada, Germany, Italy, the Netherlands, Switzerland, UK, and US) agreed on the structure, content, and wording of the research stages, quality dimensions, specific questions, and descriptive examples of the final framework. In Switzerland, INQUIRE has resulted in a roadmap that guides initiatives to increase value within the Swiss Clinical Trial Organization network and through affiliated researchers. Conclusions We present a framework based on a consensus of different stakeholder groups guiding the practical assessment of clinical research quality at all stages of a research project. Operationalization of this common structure will support the increase of value by guiding academic institutions and researchers in developing quality enhancement initiatives, from posing the right research question to the transparent publication of results.